Heterobivalent Dual-Target Peptide for Integrin-αvβ3 and Neuropeptide Y Receptors on Breast Tumor - Aryel H. Ferreira; Caroline C. Real; Osvaldo Malafaia (MDPI AG, 2024)
Background/Objectives: Heterodimer peptides targeting more than one receptor can be advantageous, as tumors can simultaneously express more than one receptor type. For human breast cancer, a promising biological target is tumor angiogenesis through αvβ3 integrin expression. Another promising target is Neuropeptide Y receptors, considering Y1R is overexpressed in 90% of human breast tumors. This article details the development and preclinical evaluation, both in vitro and in vivo, of a novel heterodimer peptide dual-receptor-targeting probe, [99mTc]HYNIC-cRGDfk-NPY, designed for imaging breast tumors. Methods: Female BALB/c healthy mice were used to perform biodistrubution studies and female SCID mice were subcutaneously injected with MCF-7 and MDA-MB-231 tumor cells. [99mTc]HYNIC-cRGDfk-NPY was intravenously administered to the mice, followed by ex vivo biodistribution studies and small-animal SPECT/CT imaging. Nonspecific tracer uptake in both models was determined by coinjecting an excess of unlabeled HYNIC-cRGDfk-NPY (100 µg) along with the radiolabeled tracer. Results: Imaging and biodistribution data demonstrate good uptake to estrogen receptor-positive (MCF-7) and triple-negative (MDA-MB-231) tumor models. The in vivo tumor uptakes of radiolabeled conjugate were 9.30 ± 3.25% and 4.93 ± 1.01% for MCF-7 and MDA-MB231, respectively. The tumor/muscle ratios were 5.65 ± 0.94 for the MCF-7 model and 7.78 ± 3.20 for MDA-MB231. Conclusions: [99mTc]HYNIC-cRGDfk-NPY demonstrated rapid blood clearance, renal excretion, and in vivo tumor uptake, highlighting its potential as a tumor imaging agent.